The Promise of Fintech : Financial Inclusion in the Post COVID-19 Era - Sahay, Ratna (Departmental Papers; Departmental Paper ;, 2020)
Technology is changing the landscape of the financial sector, increasing access to financial services in profound ways. These changes have been in motion for several years, affecting nearly all countries in the world. During the COVID-19 pandemic, technology has created new opportunities for digital financial services to accelerate and enhance financial inclusion, amid social distancing and containment measures. At the same time, the risks emerging prior to COVID-19, as digital financial services developed, are becoming even more relevant.